Z problematyki ramy literackiej w komediach plebejskich XVII w. (wybrane zagadnienia) - Pirecki, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
The paper fucuses on the problem of publishing framework in 17th century plebeian comedy. The issue has been treated in a rather general way as the approach deals with only two main elements, dedication and preface. Both the former and the latter, however, are seen as the most effective representatives of the wide literary material defined as the publishing framework.